Functional dairy products - Mattila-Sandholm, Tiina; Saarela, Maria (Woodhead Publishing in food science and technology., 2003)
Annotation Dairy products constitute one of the most important types of functional food. Edited by two of the leading authorities in the field, and with a distinguished international team of contributors, this major collection reviews the health benefits of functional dairy products, their ingredients and key product development issues. After an introductory survey of the various types of functional dairy product, Part I discusses current research on the health benefits of functional dairy products, with chapters on cancer, coronary heart disease, osteoporosis, food allergy, immune function and gastrointestinal health. Part II reviews key dairy ingredients, their functional benefits and uses, covering caseinophosphopeptides, oligosaccharides, lactic acid bacteria and conjugated linoleic acid. Finally, Part III covers product development issues ranging from enhancing the functionality of prebiotics and probiotics to safety evaluation and consumer, market and research trends in this important sector. Functional dairy products will be a standard work for food manufacturers developing new dairy products and for all those researching functional foods. Book jacket.